Metodologi Penelitian: Analisis Konseptual untuk Memahami Hakikat, Tujuan, Prosedur, dan Klasifikasi Penelitian - Nur, Zulfikah; Sulaiman, Umar; Rahman, Ulfiani (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2024)
This article aims to explore the different types of research that can be used based on the research objectives to be achieved. This research is carried out through a literature study method which is part of a qualitative approach. The main sources of research data are books and scientific articles published in scientific journals and indexed by google scholar. The keywords used in the article data generation are "research methodology", "research essence", "research procedure", and "research classification". Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that there are four characteristics of scientific research, namely systematic (a research must be compiled and carried out sequentially according to the correct pattern and rules, from easy and simple to complex), logical (the search for truth must take place according to the procedure or rules of the working of reason, namely logic), empirical (a research based on daily experience, which is found or through trial and error results that are then raised as a result of research), and replicable (a study that has been conducted must be retested by other researchers and must give the same results when carried out with the same methods, criteria, and conditions)